Identification of potential cell binding sites on the nipah virus attachment glycoprotein using phage display system / Lau Chui Wan - Lau, Chui Wan (2017)
Nipah virus (NiV) infection is initiated upon binding of the viral G glycoprotein to the host cell surface receptor, ephrin-B2 or ephrin-B3. Thus, this study was aimed to map the regions of NiV G glycoprotein that are important for cell binding by phage display system. The extracellular domain or NiV G was truncated into five different fragments, generated by reverse transcription polymerase chain reaction (RT-PCR) and cloned into a phagemid vector. These recombinant phagemids were transformed into two different Escherichia coli strains, the non-suppressor strain for production of truncated NiV G recombinant proteins in soluble form , and the suppressor strain, to display the truncated NiV G on M 13 bacteriophages g3p minor coat protein as recombinant G-g3p fusion protein. The binding efficiency or recombinant phages displaying the different regions or NiV G lo mammalian cell was evaluated. Recombinant phage G4 displaying amino acids 396-602 and recombinant phage GS displaying amino acids 498-602 demonstrated the highest binding to both Vero (5.5 x 10 cfu/ml and 5.6 x 10'cfu/ml) and THP-1 cells (3.5 x 10 cfu/ml and 2.9 x 10 cfu/ml ). However, the binding of both recombinant phages G4 and G5 to THP-1 cells was significantly lower than to Vero cells, and this could be due to the lack of host cell receptor expression on THP-1 cells. Furthermore, the binding of recombinant phages was also shown to be dependent on the amount of ephrin-B2 protein. The binding between recombinant phages G4 and G5 was competitive suggesting that there was a common host cell attachment site. In conclusion, this study demonstrated the successful display of truncated NiV G on M13 bacteriophages, the direct binding of truncated NiV G displayed on recombinant phages to cells and that the amino acids 498-602 played an important role for the host cell attachment. The phage display system enabled mapping of cell binding domains of NiV G glycoprotein under biosafety level 2 containment without the need to use live Category C virus.